Plan Estratégico de Marketing para K.P.I. Vehículos, de la Ciudad de Loja - Armijos González, Doris Del Carmen (2016)
The overall objective of this thesis is part of the development of a "STRATEGIC MARKETING PLAN K.P.I. VEHICLES, CITY OF LOJA "with its development aims to provide a clear view of the situation in which the company is to ensure their permanence and expansion in the competitive market. To carry out this research methods, techniques and procedures that enabled research, develop and test the veracity of the study were used, the methods used were: Deductive Method applied it in research to contrast relevant aspects of the facts and theories general condensates the theoretical framework and particularized specifically in drafting the proposal, the SWOT, EFE matrix, EFI matrix, IE matrix and high-impact matrix. Inductive method was employed in the study and analysis of the survey results, later to determine general conclusions reached in the investigation, also was it used in the formulation of strategies and the proposal to determine objectives, goals, activities to be carried out in the strategic plan. The research process received the support of key staff (Manager, Sales Consultant, Accountant) Patio car K.P.I. VEHICLES, direct competitors and customers of the company. The variables investigated were external (PESTEC) internal, competitive and market, using information gathering interview guides and questionnaires designed for this purpose and applied via techniques interview key officials, survey of 48 customers and observation direct competitors and research company, once collected information allowed the subsequent analysis and interpretation of results. 7 The technical scaffolding upon which the structure of the Strategic Marketing Plan cemented was tempered by compliance with the following logical process: Based on the information obtained product of the analysis of external factors could be determined according to the analysis of the EFE matrix the weighted result of 2.77 allows to know that currently the company is taking advantage of a minimum percentage the various opportunities offered by their environment, which include as most representative as follows: the stability of the dollar, revaluation of automotive used due to the quota limit imports of new vehicles, improving the current socioeconomic situation of the population. In relation to threats constitute the greatest impact: Safeguards specific taxes for buying and selling used cars, growth, strengthening and intensity of competition. In the competitive analysis conducted, it is evident that the weighted result of 3.11 in relation to the identified direct competitors is less than these, indicating that the car Patio K.P.I. VEHICLES not positioned in the sector, but it shows advantage over direct competitors on factors such as vehicle quality, market experience, competitive prices and safety and legality in the transaction. In the competitive position of the services offered it is observed that the research company excels in buying and selling services on factors such as price, warranty papers and legality of the vehicle, thorough mechanical review, specialized service. In point internal analysis is performed, which by EFI matrix whose result is 2.68 allows us to know that the company has an acceptable percentage of 8 strengths against weaknesses, finding as significant strengths competitive prices, dedicated service and quality vehicles; and as the more obvious weaknesses the company does not have a marketing plan does not provide training for the sales force, and shows a decrease in sales. In the market study carried out to customers is that: designated as relevant features of KPI vehicles for 52% of customers the good condition of the vehicles offered for a 54% price, 48% variety of vegetables and 44 % customer service. The final part of this investigation consists of SWOT analysis summarizes the analysis of the studied internal and external factors in order to identify the respective strategies, based on what the proposal was built, it contains three strategic targeted objectives to Achieve sales growth both at local and regional level in the next 3 years. Consolidate the corporate image of K.P.I. vehicles on the local and regional market marketing of used vehicles. K.P.I. expand the participation of vehicles on the market within the next 3 years. For the realization of the objectives outlined in this proposal a total investment of $ 16,450.66 was budgeted. At work finally establish the conclusions and recommendations, which are to complement satisfactorily the development of the strategic marketing plan proposed.